Visual function after penetrating keratoplasty for keratoconus: a prospective longitudinal evaluation. Issue 1 (1st January 2000) - Brahma, Arun; Ennis, Fergal; Harper, Robert; Ridgway, Alan; Tullo, Andrew
Abstract : AIMS: To evaluate visual function and vision specific health status in patients undergoing penetrating keratoplasty for keratoconus. METHODS: A prospective longitudinal study measuring logMAR visual acuity, contrast sensitivity, disability glare, binocular visual field, stereoacuity, and subjective visual function (VF-14) was conducted on 18 patients with keratoconus undergoing penetrating keratoplasty (PK), including six patients who had already had PK in the fellow eye. Data were collected preoperatively and at 3, 9, and 18 months after surgery. RESULTS: Within 3 months of surgery there was significant improvement in aided visual acuity, contrast sensitivity, and stereoacuity (p<0.05); disability glare (p<0.05) no longer had a significant detrimental effect on these variables. VF-14 score improved significantly throughout the postoperative period (p<0.05). There was significant correlation of the VF-14 score with aided visual acuity, binocular visual field, and stereoacuity. Postoperative astigmatism (<4D v >4D) did not affect the VF-14 score significantly. CONCLUSIONS: There is substantial and rapid improvement in visual function and vision specific health status in keratoconic patients as a result of uncomplicated penetrating keratoplasty.